Effect of Effective Cough on Sputum Expenditure in Pulmonary Tuberculosis Patients - Endah Dwi Lestari; Annisaa Fitrah Umara; Siti Asriah Immawati (Jurnal Ilmiah Keperawatan Indonesia [JIKI], 2020)
Background: Tuberculosis is a direct infectious disease caused by TB germs (Mycobacterium Tuberculosis). The entry of Tuberculosis bacteria will infect the lower respiratory tract which can result in productive coughing and coughing up blood. Some nursing interventions to overcome the problem of airway cleaning ineffectiveness include effective coughing exercises. Objective: This study aims to determine the effect of effective cough on sputum removal in patients with pulmonary tuberculosis. Research Methods: The study design used was Quasi Experimental Pre-test and Post-test. The population of 15 respondents included all pulmonary tuberculosis patients in Balaraja Hospital. A sample of 10 respondents was taken using Non Probability sampling. Independent variables are effective cough and dependent variable sputum expenditure Analysis of data with the Wilcoxon Match Pair Test with a significant level of a≤ 0.05. Research Results: The results showed that the majority of respondents were unable to excrete sputum before being trained in effective cough of 4 respondents (40.0%), respondents who had moderate sputum expenditure as much as 6 respondents and respondents could excrete large amounts of sputum after being trained for effective coughing by 6 respondents (60.0% ), respondents who issued a lot of medium sputum were 4 respondents (40.0%) and the results of the Wilcoxon Match Pair Test were 0.04 which meant <0.05 then Ha was accepted. Conclusion: It means that there was an effective effect of cough on sputum release in Tuberculosis patients at Balaraja Hospital. Pulmonary Tuberculosis patients by doing effective cough can save energy so it does not get tired easily and can expel phlegm optimally and is recommended one day before sputum examination, patients are advised to drink warm water to facilitate sputum removal. Keywords: Effective Cough; Pulmonary Tubercullosis; Sputum